Mesenchymal stem cell-derived exosomes ameliorate diabetic kidney disease through NOD2 signaling pathway - Yinghui Wang; Donglin Lu; Shasha Lv; Xiangchun Liu; Gang Liu (Renal Failure)
Background and aims Diabetic kidney disease (DKD) is one of the most common complications of diabetes. It is reported that mesenchymal stem cells (MSCs) derived exosomes (MSCs-Exo) may have great clinical application potential for the treatment of DKD, but the underlying mechanism has not been illustrated. To clarify the effect of MSC-Exo on NOD2 signaling pathway in podocytes under high glucose (HG) and DKD, we conduct this study.Methods We co-cultured podocytes and MSCs-Exo under 30 mM HG and injected MSCs-Exo into DKD mice, then we detected the NOD2 signaling pathway by western blot, qRT-PCT, immunofluorescence, transmission electron microscopy and immunohistochemistry both in vitro and in vivo.Results In vitro, HG lead to the apoptosis, increased the ROS level and activated the NOD2 signaling pathway in podocytes, while MSCs-Exo protected podocytes from injury reduced the expression of inflammatory factors including TNF-α, IL-6, IL-1β, and IL-18 and alleviated the inflammatory response, inhibited the activation of NOD2 signaling pathway and the expression of it’s downstream protein p-P65, p-RIP2, prevented apoptosis, increased cell viability in podocytes caused by HG. In vivo, MSCs-Exo alleviated renal injury in DKD mice, protected renal function, decreased urinary albumin excretion and inhibited the activation of NOD2 signaling pathway as well as the inflammation in renal tissue.Conclusion MSCs-Exo protected the podocytes and DKD mice from inflammation by mediating NOD2 pathway, MSCs-Exo may provide a new target for the treatment of DKD.